Addressing the Role of 2D Domains in High‐Dimensionality Ruddlesden–Popper Perovskite for Solar Cells. Issue 3 (14th December 2022) - Bravetti, Gianluca; Altamura, Davide; Paci, Barbara; Generosi, Amanda; Carallo, Sonia; Guaragno, Marco; Gigli, Giuseppe; Listorti, Andrea; Grancini, Giulia; Giannini, Cinzia; Colella, Silvia; Rizzo, Aurora
Abstract : High‐dimensionality Ruddlesden–Popper (RP) perovskites, with general formula R2 A n −1 B n X3 n +1 and high n values ( n ≥ 5), are regarded as viable materials for photovoltaics because they feature higher stability if compared to the 3D perovskite, i.e., ABX3, still maintaining good charge absorption and transport properties. When integrated into the actual solar cells, however, scattered, sometimes contradictory results are reported among different deposition procedures and different cations, especially for higher n resulting in not uniform morphology and mixed composition. Herein, high‐dimensionality RP perovskites with n = 1, 4, 10, 20, and 40 values are systematically investigated considering the interplay between the formation of 2D domains, their distribution along the active layer, the active layer thickness, and the solar cells' performance. Given the complexity of the investigated system, combined advanced structural/morphological analyses are performed to explain solar cells' performance, finding that the 2D phase segregates at the interface with the top electrode, acting as a barrier for charge extraction, overall decreasing the short‐circuit current ( J sc ). Reducing the relative amount of bulky alkylammonium cation with respect to the methylammonium, the 2D perovskite overlayer is intentionally decreased leading to a recovery of the J sc values, corroborating the hypothesis. Abstract : High‐dimensionality Ruddlesden–Popper perovskites are investigated by considering 2D domains formation, thickness, distribution along the active layer, and the solar cells' performance. Combined advanced structural/morphological analyses are performed, finding that the 2D phase segregates at the interface with the top electrode, acting as a barrier for charge extraction, overall decreasing the short‐circuit current.